2007
DOI: 10.1017/s000711450770908x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nucleic acids and nucleotides are efficiently hydrolysed and taken up as nucleosides by intestinal explants from suckling piglets

Abstract: Human milk is a rich source of RNA, free nucleotides (NT) and nucleosides (NS). To determine the uptake of different NS sources by the intestinal epithelium, jejunal explants from suckling piglets were cultured in a medium supplemented with a mixture of NS (adenosine, cytidine, guanosine, inosine, uridine; 10 mg/l each), a mixture of five NT (AMP, CMP, GMP, IMP, UMP; 7 mg/l each) or RNA (60 mg/l), respectively. Aliquots from the media were taken at different times (0·5, 2, 5, 15, 30, 60, 180 min). NS and NT co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…According to the present findings, proliferating and differentiated IEC-6 cells control the selective uptake of NS (Table 1). Our group recently reported that hepatocytes 10 , 11 and intestinal explants 12 are capable of selective NS uptake. The present results showed that the rate of uridine and purine NS clearance in IEC-6 cells was similar to that of adult hepatocytes 10 and of intestinal explants 12 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the present findings, proliferating and differentiated IEC-6 cells control the selective uptake of NS (Table 1). Our group recently reported that hepatocytes 10 , 11 and intestinal explants 12 are capable of selective NS uptake. The present results showed that the rate of uridine and purine NS clearance in IEC-6 cells was similar to that of adult hepatocytes 10 and of intestinal explants 12 .…”
Section: Discussionmentioning
confidence: 98%
“…In hepatic cells, our group showed that exogenous NS were actively incorporated by hepatocytes and stimulated hepatocyte proliferation and expression of c-myc, h-ras genes and a-fetoprotein 10,11 . Gil et al 12 recently showed that intestinal explants hydrolyse RNA to NT, and NT to NS that were efficiently incorporated into intestinal cells, except for cytidine. Reports on the effect of NT in intestinal cell proliferation and differentiation are contradictory.…”
mentioning
confidence: 99%
“…All foods contain varying amounts of nucleic acids and NT that release NS after digestion. NS are a dephosphorylated form of NT that can be more effectively absorbed by the enterocyte via specific transporter proteins in comparison to NT or nitrogen bases [Ho et al, 1979;Gil et al, 2007]. In the other type of synthesis, NT can be synthesized de novo from simple molecules such as 5-phosphoribosyl-1-pyrophosphate for purines and glutamine for pyrimidines, although this implies an important consumption of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous NT and NS increase intracellular NT pools of enterocytes [Gil et al, 2007], augment brush border enzyme activity [Van Buren et al, 1982;Uauy et al, 1990], modulate their gene expression [Sanderson and Walker, 1993] and prevent the progress of intestinal mucosal atrophy under total parenteral nutrition conditions [Iijima et al, 1993]. Exogenous NT also reduce the adverse effects associated with intestinal disorders such as irritable bowel syndrome [Dancey et al, 2006] and may therefore represent a novel therapeutic approach to maintaining gastrointestinal tract integrity [Rodríguez-Serrano et al, 2007a].…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotides and nucleic acids are constantly being formed and degraded in all tissues, especially in tissues with a rapid turnover rate such as cells in the immune system, intestinal mucosa, skin, and progenitors of leucocytes or erythrocytes ( 7 ) . For example, according to an in vitro study on intestinal explants from suckling piglets, the jejunum of piglets at weaning is able to hydrolyse RNA and free nucleotides to nucleosides, which, except for cytidine, are then efficiently taken up by the small intestine ( 21 ) . Generally, there are three potential sources of nucleotides: de novo synthesis, salvage pathways and the diet ( 8 , 22 ) .…”
Section: Biochemical and Functional Characteristics Of Nucleotidesmentioning
confidence: 99%